Love of Money and Adversity Quotient: Catalyzers of Entrepreneurial Intention of MSME Actors in Semarang City - Alifa Putri Hervina; Laila Listiana Ulya (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Being an MSME entrepreneur is not easy because of the various obstacles and risks, which require strong entrepreneurial intentions to survive. MSME entrepreneurs must be adaptive to the business challenges that they needadversity quotientto turn limitations into opportunities andlove of moneythat encourages entrepreneurial intentions through money. This research was conducted to determine the effect oflove of moneyandadversity quotienton entrepreneurial intention by involving 384 MSME entrepreneurs in Semarang City who fulfilled the MSME criteria based onGovernment Regulation No. 7 of 2021. The number of subjects was determined through Lemeshow's formula using a sampling error of 5%. The subjects came from various MSME communities such as, Semarang City Cooperatives and MSMEs ServiceTraining Participants, FOKKUS Great Organization, Semarang Community Ambassador Cooperativeand UNNES area MSME entrepreneurs. The analysis was conducted with PLS-SEM via SmartPLS-4. The results showed thatlove of moneyandadversity quotienthad a significant effect on entrepreneurial intention with a p-value ≤ 0.05 and t-statistic ≥ 1.96. Adversity quotienthas an effect of 0.574 (57.4%). andlove of moneyhas an effect of 0.179 (17.9%) in the establishment of entrepreneurial intentions of MSME entrepreneurs. This indicates that rather than the money factor to get the desired money, the ability to deal with various problems plays a greater role in the entrepreneurial intention of MSME entrepreneurs in Semarang City.